Large‐surface‐area diamond (111) crystal plates for applications in high‐heat‐load wavefront‐preserving X‐ray crystal optics. (10th August 2016) - Stoupin, Stanislav; Antipov, Sergey; Butler, James E.; Kolyadin, Alexander V.; Katrusha, Andrey
Abstract : Fabrication and results of high‐resolution X‐ray topography characterization of diamond single‐crystal plates with large surface area (10 mm × 10 mm) and (111) crystal surface orientation for applications in high‐heat‐load X‐ray crystal optics are reported. Abstract : Fabrication and results of high‐resolution X‐ray topography characterization of diamond single‐crystal plates with large surface area (10 mm × 10 mm) and (111) crystal surface orientation for applications in high‐heat‐load X‐ray crystal optics are reported. The plates were fabricated by laser‐cutting of the (111) facets of diamond crystals grown using high‐pressure high‐temperature methods. The intrinsic crystal quality of a selected 3 mm × 7 mm crystal region of one of the studied samples was found to be suitable for applications in wavefront‐preserving high‐heat‐load crystal optics. Wavefront characterization was performed using sequential X‐ray diffraction topography in the pseudo plane wave configuration and data analysis using rocking‐curve topography. The variations of the rocking‐curve width and peak position measured with a spatial resolution of 13 µm × 13 µm over the selected region were found to be less than 1 µrad.